Pengaruh Skema Kompensasi Dan Self Efficacy Terhadap Budgetary Slack: Sebuah Studi Eksperimen - Mesrawati Candra; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to prove empirically about: 1) differences in the effect of truth inducing and slack inducing compensation schemes on budgetary slack, 2) differences in the effect of high and low self efficacy on budgetary slack, 3) the effect of interaction compensation schemes and self efficacy on budgetary slack. This study uses a quasi-experimental method with a group of research subjects who are students majoring in Accounting in the 2016 bachelor year of the Faculty of Economics, Padang State University. The sampling technique is total sampling. The population in this study amounted to 107 students. The source of research data is primary data using working paper in the form of coding or translating letters into numbers. Data analysis using two ways ANOVA test. The results of this study concluded that compensation schemes can affect lower-level managers in conducting budgetary slack, self-efficacy affects lower-level managers in conducting budgetary slack, and the influence of interaction compensation and self-efficacy schemes on budgetary slack